New species and new synonym of Necrosciini (Phasmatodea: Lonchodidae: Necrosciinae) from Hainan Province, China - Wen, Jun; Qian, Yu-Han; Xie, Chong-Xin; Chen, Rui; Wang, Chen (Zootaxa, 2024)
This paper describes a new species Parasinophasma ledongense sp. nov. of the genus Parasinophasma Chen & He, 2006. The diagnostic characters of the new species are illustrated, and an identification key is provided for males and females of the genus. In addition, we show that Sipyloidea wuzhishanensis (Chen & He, 2002) is a junior synonym of Huananphasma amicum (Bey-Bienko, 1959).